Safe miner Android Application - Machakaire, Thelma (Midlands State University, 2020)
Due to the current economic situation and the growth in world demand, the mining industry is undergoing a period of spectacular development. The current need to increase production at mine sites coincides with the development of managerial capacities, the use of new industrial methods and equipment, and increased use of skilled workforce. Despite such developments, a number of researchers view the mining sector among the world’s most uncertain and hazardous industries. Therefore, the major problem is, in Zimbabwean market there is no effective system that allows miners to access manuals, work schedules, maps and location easily wherever they are. Development of this project remains a goal to be attained so as to enhance reliability of decisions and make mining organizations safer and more secure. The developer further investigated how the current systems work and in-depth understanding of the problem area was gained through the use of interviews, observations and questionnaires. The system comprised of android application developed in android studio. A literature review was conducted so as to provide a strong foundation for advancing knowledge about the project, overview of the mining sector was provided and how mining is carried out in the mines and a list of the mining products. Technology is changing rapidly and there is need to adjust so as to improve the economy and how businesses operate in Zimbabwe, technology has impacted the mining sector in a positive way and modifications were made to the mining sector. There is no doubt that the future landscape of mining will be a digital landscape soon. Companies must invest in tools and analytics that will allow them to become a modern digital mining company. The future will be digital that is, digital camera, videos, electronic document storage, network data collection, intelligent search software to see trends and optimise operations. The dissertation also focused on the actual system design structure to clarify how the system works, architectural design, physical design of the developed system, database design, program design which is explained through the package and class diagrams, interface design of the system. The application was tested and deployed successfully.